Fertilizer Recommendation for Four Crop Based Cropping Pattern: Potato- Boro- T. Aus-T. Aman Under AEZ – 11 (Bangladesh Agronomy Journal, 2020)
A field experiment on Potato-Boro-T. Aus-T. Aman cropping pattern was conducted in the High Ganges Floodplain Soil of Jashore (AEZ - 11) during 2014-2015 and 2015-2016 to find out optimum fertilizer management for intensive cropping attern, in relation to soil health.There were eight different treatments viz. T1=100% NPKSZnB (STB= Soil Test Based), T2=T1 + 25% N, T3=T1 + 25% NP, T4=T1 + 25% NK, T5=T1 + 25% PK, T6=T1 + 25% NPK, T7=75% of T1, and T8=Native fertility (control) as individual crop management. The experiment was laid out in randomized complete block design with three replications. Results revealed that the tuber yield of potato, grain yields of boro, T. Aus and T. Aman were significantly influenced by the fertilizer treatments. The maximum tuber yield (25.70 and 24.80 t ha-1), grain yields of boro (6.50 and 6.31 t ha-1), T. Aus (3.13 and 3.10 t ha-1) and T. Aman (3.95 and 3.98 t ha-1) was obtained from the T6 treatment where 25% additional NPK was added with 100% STB in both the year. These yields weretatistically similar with that produced by all other fertilizer treatments except the native fertility treatment. Highest rice equivalent yield (REY) of 12.63 t ha-1 was obtained from T6 treatment whereas lowest REY of 5.93 t ha-1 was obtained from control.Bangladesh Agron. J. 2019, 22(1): 71-78